Implementation of Banten Debus Art in SBK Lessons at MIN 2 Serang Regency - Tresnawati, Astri; Pebrianti, Bella (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This study aims to describe the implementation of Banten Debus art in Arts, Culture and Skills (SBK) learning at MIN 2 Serang Regency, as well as to analyse the cultural values and character contained therein. This study uses a qualitative approach with a descriptive method. Data was obtained through interviews, observations, and documentation of SBK teachers, the head of the madrasah, and students in grades IV–VI. The results of the study show that teachers strive to integrate local cultural elements into learning through a contextual approach, by introducing the history, philosophical values, and symbolic meanings of Debus art. The implementation was carried out through stages of introduction, exploration, and expression that encouraged creativity and students' understanding of the values of courage, faith, and discipline. Debus-based learning has been proven to increase students' motivation and pride in their regional culture. However, there are obstacles in the form of limited learning resources and a lack of training for teachers in developing local culture-based learning. This study concludes that Banten Debus art is effective as a medium for local wisdom-based learning that can strengthen Islamic character education and preserve regional culture in madrasahs.